Immune Responses Following BCG Immunization of Infants in Uganda and United Kingdom Are Similar for Purified Protein Derivative but Differ for Secretory Proteins of Mycobacterium tuberculosis - Mawa, Patrice A.; Hasso-Agopsowicz, Mateusz; Lubyayi, Lawrence; Nabakooza, Grace; Nakibuule, Marjorie; Blitz, Rose; Dun, Li; Govind, Abha; Kaleebu, Pontiano; Webb, Emily L.; Elliott, Alison M.; Dockrell, Hazel M.; et al. (Frontiers in Immunology, 2021)
Introduction: The immunogenicity of BCG vaccination in infants differs between populations. We hypothesised that prenatal exposure to mycobacterial antigens might explain the differences in immune responses to BCG seen in other studies of infants in Africa and the United Kingdom (UK) and we explored this in birth cohorts in Uganda and the UK. Materials and Methods: Blood samples were obtained from BCG-immunised infants of mothers with (n=110) and without (n=121) latent Mycobacterium tuberculosis (M.tb) infection (LTBI) in Uganda and BCG-immunised infants of mothers without LTBI (n=25) in the UK at 10 and 52 weeks after birth. Cytokine and chemokine responses to PPD were measured to assess responses to BCG immunisation, and to ESAT6/CFP10 to assess exposure to or infection with M.tb or non-tuberculous mycobacteria (NTM) in 6-day whole blood culture supernatants by a 17-plex Luminex assay. Median responses were compared between Ugandan infants (together, and separated by maternal LTBI status) and UK infants. Results: The IFN-γ response to BCG vaccination was similar between Ugandan and UK infants at 10 and 52 weeks. At week 52, TNF production was marginally higher in Ugandan infants, but after adjusting for multiple comparisons this difference was not significant. At weeks 10 and 52, stimulation of blood with ESAT6/CFP10 produced significantly higher IFN-γ, TNF, IL-12p40, IL-1α, IL-1β, IL-1Ra, IP-10, MIP-1α, MIP-1β and GM-CSF in Ugandan compared to UK infants. Stimulation of blood with ESAT6/CFP10 produced significantly higher amounts of IL-8 (p=0.0001), IL-10 (p=0.0022) and IL-13 (p=0.0020) in the UK than in Ugandan infants of mothers without LTBI at week 10, but not at week 52. Conclusions: Immune responses to mycobacterial antigens following BCG immunisation are similar for PPD, but differ for ESAT6/CFP10, between infants in Uganda and the UK. Neither maternal LTBI nor infant exposure to or infection with mycobacteria impacts the response to BCG. The observed global differences in immune response to BCG immunisation are likely to be due to other causes.